Analisis Penjadwalan Proyek Pembangunan Jaringan Fiber Optik Menggunakan Metode Critical Path Methode (CPM) di Lemo - Lemo Bulukumba - Fadli, Feri (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
This research aims to analyze the scheduling of the fiber optic network construction project in Lemo-Lemo, Bulukumba, using the Critical Path Method (CPM). This method was chosen to improve time and cost efficiency in project implementation. Research data were obtained through field observations, literature studies, and interviews with related parties. Analysis was carried out by mapping project activities, estimating duration, and calculating resource requirements and project costs. The results showed that the application of the CPM method was able to accelerate project completion from the initial estimate of 40 days to 21 days, with time savings of 19 days. In addition, the project cost which was initially estimated at Rp. 38,386,680 was successfully reduced to Rp. 37,000,000, resulting in a savings of Rp. 1,386,680. In conclusion, the CPM method proved to be effective in improving time and cost efficiency in fiber optic network construction projects. Therefore, it is recommended that this method be applied consistently in similar projects in the future.